Kinetic Investigation of Reaction Between Colemanite Ore and Methanol - Kizilca, Meltem; Çopur, Mehmet (Taylor & Francis Inc, 2015)
In the field of industry, it is very important that boron compounds are produced from boron ores. The aim of this study was to investigate the dissolution kinetics with carbon dioxide of colemanite in methanol medium in a pressure reactor and to derive an alternative process for producing boron compounds. Reaction temperature, stirring speed, solid/liquid ratio, pressure, and particle size were selected as parameters for the dissolution rate of colemanite. It was found that the dissolution rate increased with increase in pressure and reaction temperature, and with decrease in particle size and solid/liquid ratio. No effect of stirring speed was observed on conversion. The dissolution kinetics of colemanite were examined using both heterogeneous and homogeneous reaction models, and it was determined that the reaction rate can be described by a second-order pseudo-homogeneous reaction model. The activation energy was found to be 51.4 kJ/mol.
Keywords: Activation energy; Boron compounds; Colemanite; Dissolution kinetics; Dissolution rate; Methanol